KNOWLEDGE, ATTITUDE, AND PRACTICE TOWARDS HEPATITIS B AMONG UNIMAS UNDERGRADUATE NURSING STUDENTS - JOELIANA, RAMLEE (Universiti Malaysia Sarawak (UNIMAS), 2023)
Introduction: Nursing students were at higher risk of acquiring Hepatitis B infection during clinical attachments. Therefore, comprehensive teachings and trainings were well-needed to improve the students’ Hepatitis B preventive practices. Objective: To assess the level of knowledge, attitude, and practice towards Hepatitis B among UNIMAS undergraduate nursing students as well as to determine any correlation between knowledge, attitude, and practice among UNIMAS undergraduate nursing students. Method: It is a quantitative, descriptive cross-sectional study that use self-administered questionnaire to collect the data among a simple random sample of 146 student nurses. The data was analysed using Spearman Correlation test. Result: Most of the respondent’s age range between 19 to 25 years old (M= 21.76, SD= ±1.261). UNIMAS nursing students' knowledge of Hepatitis B was determined to be moderate with a mean score overall of 56.11 and a standard deviation of 5.888. The study discovered that half of the respondents (52.1%, n=76) have insufficient understanding on hepatitis B, whereas the other half (47.9%, n=70) have adequate knowledge. With an overall mean score of 9.86 and a standard deviation of 0.169, the attitude level towards Hepatitis B among UNIMAS nursing students was determined to be moderate. The majority of respondents (61.6%, n=90) had negative attitudes pertaining to hepatitis B, whereas just 38.4% (n=56) had positive attitudes. The researcher found that majority of the respondents has exhibits poor practices towards Hepatitis B (55.5%, n=81) meanwhile, only 44.5% (n=65) of them has a satisfactory practice level towards Hepatitis B. Levels of attitude and knowledge showed a weak but statistically significant positive correlate (r=0.219, p=0.008). The level of knowledge and level of practice did, however, show a moderate and statistically significant positive correlation (r=0.450, p<0.05). On the other hand, there was only a very weak correlation between attitude level and practise level (p > 0.05), which was not statistically significant. Conclusion: It can be stated that the majority of the UNIMAS undergraduate nursing students scored in the middle range for both knowledge and practice. On the other side, UNIMAS undergraduate nursing students scored poorly on attitude items. Therefore, theoretical and practical instruction must be given concurrently in order for nursing students to receive enough knowledge and guidance in handling Hepatitis B patients in the clinical setting.